Analysis of Quality Control of 800ml Lubricant Bottle Leaks with Seven Tools Method at PT. EFG - Gustany, Eko Widodo; Hariyanto, AL; Haryudiniarti, Ayu Nurul (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
PT EFG is a lubricant company that maintains customer satisfaction by producing quality products, starting from supply of raw materials, production process until final product. Company tries to minimize damage, but there are still many leaking products and not according to standards. This study aims to control quality using seven tools method to reduce leaking bottles of 800ml size, from January-October 2022, the biggest is fish eyes. The highest amount of damage occurred in June at 0.0039%, exceeding the maximum damage limit of 0.003%. Improvements are divided by external and internal. External, from the supplier are cleaning the mold cavity, cleaning remaining material on the mold, and maintaining the cleanliness of plastic seeds. Suppliers ensure the leak tester are detected and not sent to PT EFG. Internal, are carried out by improving the leak detection of the led light table machine and changing the random sampling method when material incoming from suppliers.